ETMR-14. The single-cell landscape of pineoblastoma identifies developmental origins and exposes novel therapeutic vulnerabilities. (3rd June 2022) - Gudenas, Brian; Englinger, Bernhard; Liu, Anthony P Y; Ahmad, Sheikh Tanveer; Meredith, David; Pfaff, Elke; Paul, Leena; Hadley, Jennifer; Batts, Melissa; Klimo, Paul; Boop, Frederick A; Gajjar, Amar; et al.
Abstract: Pineoblastoma (PB) is a rare and aggressive childhood brain tumor with highly variable age and treatment-associated outcomes. Our recent bulk tumor analyses of DNA methylation and mutational landscapes uncovered four discrete PB molecular subgroups (PB-miRNA1, PB-miRNA2, PB-MYC/FOXR2, and PB-RB), providing a major advance in our understanding of biological and clinical heterogeneity. However, developmental origins of PB subgroup heterogeneity and mechanisms governing how specific genetic alterations promote malignancy remain unknown. To resolve the cellular origins of PB, we assembled a large single-nucleus RNA-sequencing cohort (n=32) of primary PB tumors, including representatives from each subgroup. Transcriptomic analysis identified subgroup-specific gene expression programs driving intra-tumoral heterogeneity. In addition, we discovered substantial differences in the expression of miRNA biogenesis genes between the PB-miRNA1 and PB-miRNA2 subgroups, providing mechanistic support for their distinct subgroup identities despite overlapping driver events. The MYC/FOXR2 subgroup was characterized by over-expression of the FOXR2 proto-oncogene in bulk RNA-seq, which we validated in single-nuclei and identified co-expressed downstream target genes. To map PB subgroups to their putative developmental beginnings, we created a single-cell transcriptional atlas of the murine pineal gland across 11 developmental stages (E11-P21). Trajectory inference within the developing pineal gland revealed a differentiation continuum of early, mid, and mature alpha-/beta pinealocytes. Cross-species correlation and deconvolution identified significant associations between multiple PB subgroups and specific differentiation states of the pinealocyte lineage, suggestive of developmental origins. Characterization of pinealocyte development informed generation of biologically faithful disease models, including a novel genetically engineered mouse model of the PB-RB subgroup. PB-Rb1 mouse tumors were histologically and molecularly validated for their fidelity to human tumor counterparts, exhibiting up-regulation of key pinealocyte lineage markers that are diagnostic in patients. Finally, high-throughput drug screening identified several promising pharmacological candidates that may attenuate consequences of Rb1 deficiency in affected children.